Color-adjustable phosphors Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ impact on luminescence of white light-emitting diodes - My Hanh Nguyen Thi; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
We used the ceramic approach to synthesize a sequence of Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ within our study. Especially, the attributes of Sr4La(PO4)3O that were extensively investigate are luminous characteristics, thermal stableness, and energy transfering from Ce3+ to Tb3 and Mn2+.Through energy transfer, sensitizer Ce3+ ions can considerably boost the fragile green radiation from Tb3+ and red radiation from Mn2+. The color of the radiation can be changed by adjusting the Ce3+/Tb3+ and Ce3+/Mn2+ ion ratios. The Sr4La(PO4)3O: 0.12Ce3+, 0.3Mn2+ specimen produced white light having hue coordinates of (0.3326, 0.3298). According to this result, it shows that Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ might be used in white light-emitting diodes (WLEDs).